The Impact of Laboratory Staff Training on Reducing Error Rates in Clinical Laboratories - Zainab Kamil Chassab Abd Alhuseen; Noor Hamza Hussein Kazim; Ayat Mohammed Nahi Brih; Ola Shaheed Abed Arkan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Laboratories play a crucial role in ensuring patient safety, with approximately 80–90% of clinical diagnoses relying on laboratory test results. Despite their importance, laboratory errors are reported to occur in about 0.012% to 0.6% of all tests conducted. Patient safety is fundamentally a managerial responsibility that can be improved through the implementation of robust systems aimed at detecting and addressing quality deficiencies. A reactive approach to this involves incident reporting followed by root cause analysis, which helps uncover and rectify weaknesses in existing policies and procedures. Alternatively, a proactive strategy such as Failure Mode and Effects Analysis (FMEA) focuses on evaluating the entire testing process, anticipating potential adverse events, and taking preventive measures before such issues arise. This method is particularly effective for prospective risk assessment in high-risk procedures, thereby minimizing the likelihood of errors within laboratories and other areas of patient care.